Compression of the Distal Common Bile Duct by Enlarged Inferior Pancreaticoduodenal Artery Branches in a Patient with Celiac Trunk Stenosis: A Case Report - Çolaklar, Anıl; Kuru Öz, Diğdem; Erden, Ayşe (Journal of Gastrointestinal and Abdominal Radiology, 2022)
Various benign and malignant pathologies/conditions can cause compression of the extrahepatic biliary system. Anatomical and/or topographic variations of the hepatic artery have long been recognized as a possible cause of the EBS compression. However, anatomical and/or topographic variations, other than the hepatic artery's, should also be considered during the evaluation of the EBS compression. We, herein, report a unique case of the distal common bile duct compression by tortuous and enlarged inferior pancreaticoduodenal artery branches due to severe stenosis of the celiac trunk orifice.
Keywords: common bile duct; compression; inferior pancreaticoduodenal artery; magnetic cholangiopancreatography